Application of Nanoporous Super Thermal Insulation Material in the Prevention and Control of Thermal Hazards in Deep Mining of Metal Mines. (9th May 2022) - Xiao, Yigai; Deng, Hongwei; Xie, Zhimou; He, Wei
Abstract : As an important energy material, mineral resources have an important role in the rapid growth of the national economy. In recent years, with the enhancement of mining strength and the improvement of mechanized production level, the depth of mining has also increased year by year. Therefore, the number of heat hazards in deep mine mining has increased year by year, and the problem of heat loss in deep mines has become increasingly prominent, which has seriously affected the safe and efficient production of mines. In this paper, the application of nanoporous super insulation materials in the prevention of thermal damage in deep mining of metal mines is studied, and the related theories of nanoporous super insulation materials and the prevention of thermal damage in deep mining of metal mines are understood on the basis of literature data. Nanoporous thermal insulation materials refer to thermal insulation materials with pore diameters in the nanometer range. This material can effectively prevent the collision of gas molecules and prevent the heat conduction of the gas. Then, the application experiment of nanoporous super thermal insulation materials in the prevention and control of heat damage in deep mining of metal mines is carried out. Through experiments, it is concluded that the room temperature thermal conductivity of the experimental material decreases with the increase of the addition of SiO2 aerogel, and the downward trend is linear, and when the heat source temperature is 200°C, the coating surface temperature of the thermal insulation material (excluding aerogel) is 100°C, and the thermal insulation temperature difference is 100°C, while when the coating surface temperature of the aerogel thermal insulation coating is only 60°C, the thermal insulation temperature difference is 140°C. From these data, it can be seen that the thermal insulation performance of nanoporous super thermal insulation materials is better, which verifies the feasibility of its application in the prevention of heat damage in metal mine mining.